2022
DOI: 10.1002/ajh.26528
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of cytomegalovirus‐positive pediatric acute lymphoblastic leukemia at diagnosis

Abstract: Double vs single autologous stem cell transplantation for newly diagnosed multiple myeloma: long-term follow-up (10-years) analysis of randomized phase 3 studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 9 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…In prior studies, we found that approximately half of ALL cases have CMV DNA present in the bone marrow at diagnosis further suggesting that CMV could contribute to ALL development 4,22 . Congenital CMV infection occurs in 0.5% to 1.3% of children in the United States 23 . Severe sequelae such as neurologic deficits, hearing loss and liver dysfunction are features of a congenital CMV infection, but <10% of children with congenital CMV will exhibit these signs and symptoms, and the majority of children are asymptomatic at birth 23 .…”
Section: Introductionmentioning
confidence: 92%
“…In prior studies, we found that approximately half of ALL cases have CMV DNA present in the bone marrow at diagnosis further suggesting that CMV could contribute to ALL development 4,22 . Congenital CMV infection occurs in 0.5% to 1.3% of children in the United States 23 . Severe sequelae such as neurologic deficits, hearing loss and liver dysfunction are features of a congenital CMV infection, but <10% of children with congenital CMV will exhibit these signs and symptoms, and the majority of children are asymptomatic at birth 23 .…”
Section: Introductionmentioning
confidence: 92%
“…7 Instead, the immunophenotypically similar ALL subtype characterized by the ETV6-RUNX1 translocation commonly displays the APOBEC signature, 7 despite its comparatively lower prevalence of CMV. 5 This mutational signature being a broad feature of other virally induced cancers suggests the potential for other viral involvement (apart from CMV) in the cause of the ETV6-RUNX1 subtype;…”
Section: Openmentioning
confidence: 99%
“…4 Although the original neonatal results (Francis et al 3 ) were not replicated overall, the data are compatible with a recent observation that the frequency of CMV in ALL blasts at diagnosis is enhanced specifically in the HeH subtype when compared with other subtypes. 5 Additional supportive clinical evidence for the CMV-ALL association was provided from Swedish registries where CMV infection diagnosed during pregnancy in the mother of children who contracted hematologic malignant neoplasms, or at birth in the newborn, was observed at a more than 10-fold higher frequency when compared with the remainder of the age-matched population. 6 In sum, the evidence supporting an association between CMV and ALL is tantalizing and mounting rapidly, but much additional research attention is required to mechanistically describe pathways by which CMV may influence leukemia before the virus could be considered a potential target for prevention or clinical management of ALL.…”
mentioning
confidence: 97%
“…Our findings suggest a CMV-ALL association may be specific to hyperdiploid ALL, consistent with recent reports from diagnostic specimens. 29…”
Section: Jama Network Open | Hematologymentioning
confidence: 99%